THEORETICAL ASPECTS OF IMPROVING THE EFFECTIVENESS OF THE EDUCATIONAL PROCESS BASED ON THE INTEGRATION OF EDUCATIONAL TECHNOLOGIES - Karimova Madinabonu (Scholars Digest Publishing, 2025)
This article highlights the theoretical foundations of increasing the efficiency of the learning process through the integration of various pedagogical technologies in modern education. It is scientifically substantiated that the integration of educational technologies contributes to activating students’ cognitive activity, developing independent thinking skills, and enhancing interactive cooperation between teachers and learners during the lesson. The article also analyzes the importance of instructional design, technological approaches, innovative pedagogical environments, and the use of digital educational resources. The research results show that the complex application of educational technologies is a significant methodological factor in improving the quality indicators of the learning process.
Keywords: Educational technologies, integration, innovative pedagogy, digital environment, methodological approach, interactive instruction, learning process efficiency, communicative competence, pedagogical collaboration.